Anansi boys [compact disc, unabridged] - Gaiman, Neil (Gaiman, Neil. American gods., 2005)
His past marked by his father's embarrassing taunts and untimely death, Fat Charlie meets the brother he never knew and is introduced to new and exciting ways to spend his time.